ANALISIS LAPORAN KEUANGAN UNTUK MENILAI KINERJA KEUANGAN PADA PT TELEKOMUNIKASI INDONESIA Tbk TAHUN 2014 – 2015 BERDASARKAN KEPUTUSAN MENTERI BUMN NOMOR: KEP-100/MBU/2002 TENTANG PENILAIAN TINGKAT KESEHATAN BADAN USAHA MILIK NEGARA - Bambang Widarno, Fifi Ergiyanti, Suharno & (Jurnal Akuntansi dan Sistem Teknologi Informasi, 2017)
Financial ratio analysis to help determine the level of financial performance isgood or otherwise. The purpose of this study was to analyze financial performancePT Telekomunikasi Indonesia Tbk Year 2014-2015 by the Minister of State-OwnedEnterprises No. KEP-100 / MBU / 2002 on Evaluation of Health State-OwnedEnterprises in terms of the ratio of reward to shareholders (ROE), RewardsInvestment (ROI), Cash Ratio, Current Ratio , Collection Periods, InventoryTurnover, total asset Turnover, and the ratio of equity capital to total assets. Thisresearch is a case study on PT Telekomunikasi Indonesia Tbk years 2014-2015. Thedata used is the quantitative and qualitative data. Sources of data in the study usingsecondary data. Secondary data in this study of the financial statements.Telekomunikasi Indonesia Tbk, which is obtained through the website of IndonesiaStock Exchange data collection methods were used: documentation. Data analysistechnique used to use descriptive analysis. In conclusion that: (1) performanceappraisal PT Telekomunikasi Indonesia Tbk in 2014 earned a score of 62,6, or89,43% of the total score should have been 70, based on the assessment of the levelof Health State-owned PT Telkom is in the category AA 80 < TS <= 95 with healthyvalues. (2) performance appraisal PT Telekomunikasi Indonesia Tbk in 2015 gained63,1, or 90,14% of the total is supposed to be 70, based on the assessment of thelevel of Health State-owned PT Telkom is in the category AA 80 < TS <= 95 withhealthy values. (3) the performance of PT Telekomunikasi Indonesia Tbk from 2014to 2015 has increased, which in 2014 earned a score of 62,6 to 89,43% by value orhealthy, and in 2015 earned a score of 63,1 or 90,14% with a healthy value.Keywords: ROE, ROI, Cash Ratio, Current Ratio, Collection Periods, InventoryTurnover, Total Asset Turnover, the ratio of equity capital to total assets.